Perceptions of Ghanaian traditional health practitioners, primary health care workers, service users and caregivers regarding collaboration for mental health care - Solomon Nyame; Edward Adiibokah; Yasmin Mohammed; Victor C. Doku; Caleb Othieno; Benjamin Harris; Oye Gureje; Seedat Soraya; John Appiah-Poku (BMC, 2021)
Abstract Background In low- and middle-income countries, the paucity of conventional health services means that many people with mental health problems rely on traditional health practitioners (THPs). This paper examines the possibility of forging partnerships at the Primary Health Care (PHC) level in two geopolitical regions of Ghana, to maximize the benefits to both health systems. Methods The study was a qualitative cross-sectional survey. Eight (8) focus group discussions (FGDs) were conducted between February and April 2014. The views of THPs, PHC providers, service users (i.e. patients) and their caregivers, on the perceived benefits, barriers and facilitators of forging partnerships were examined. A thematic framework approach was employed for analysis. Results The study revealed that underlying the widespread approval of forging partnerships, there were mutual undertones of suspicion. While PHC providers were mainly concerned that THPs may incur harms to service users (e.g., through delays in care pathways and human rights abuses), service users and their caregivers highlighted the failure of conventional medical care to meet their healthcare needs. There are practical challenges to these collaborations, including the lack of options to adequately deal with human rights issues such as some patients being chained and exposed to the vagaries of the weather at THPs. There is also the issue of the frequent shortage of psychotropic medication at PHCs. Conclusion Addressing these barriers could enhance partnerships. There is also a need to educate all providers, which should include sessions clarifying the potential value of such partnerships.